2015
DOI: 10.3390/su7055171
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Dissemination of Organic Rice Cultivation in Bali, Indonesia

Abstract: Abstract:Organic farming has attracted attention in Indonesia because consumers increasingly prefer the putative safety and health benefits of organic farm products. Although national standards for organic farm products were established in 2002, some products sold as organic products in supermarkets do not carry the certification mark. This study investigated organic rice farming on the island of Bali in Indonesia using fieldwork to ascertain the actual increase in organic farming. Results revealed that govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
(6 reference statements)
0
14
0
3
Order By: Relevance
“…The national Indica varieties used are such as Ciherang (49.6%), Cigeulis (31.7%), IR-64 (2.1%), Inpari 13 (10.2%), and others (7.3%). Even though local varieties have lower productivity than national varieties, some farmers planted local varieties, like Ijo Gading and brown rice, due to their taste preferences and religious ceremonial requirement [25]. In other provinces, Menthikwangi, local variety in Yogyakarta, is referenced by farmers in that region.…”
Section: Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The national Indica varieties used are such as Ciherang (49.6%), Cigeulis (31.7%), IR-64 (2.1%), Inpari 13 (10.2%), and others (7.3%). Even though local varieties have lower productivity than national varieties, some farmers planted local varieties, like Ijo Gading and brown rice, due to their taste preferences and religious ceremonial requirement [25]. In other provinces, Menthikwangi, local variety in Yogyakarta, is referenced by farmers in that region.…”
Section: Cultivationmentioning
confidence: 99%
“…Price volatility sometimes happens to the organic rice market, but not significantly to other products like vegetables and fruits. In Bali, there was a lack of recognition related to certification and organic product labeling [25]. The products that stick by organic label had a significantly higher price than conventionally rice.…”
Section: Trading System and Marketmentioning
confidence: 99%
“…Rice is a staple food for at least half of the world population and for the majority of Indonesian people [1]. The rice consumption is increasing every year due to the growth of population and economic development [2]. Therefore, rice production becomes a priority of the agricultural development of the Indonesian government as rice is not only an agricultural commodity but also a symbol of sovereignty.…”
Section: Introductionmentioning
confidence: 99%
“…The "back to nature" lifestyle was emerged and people are more conscious about the negative impact of agro-chemical inputs (Jahroh 2010). Likewise, Shiotsu et al (2015) revealed that organic farming has attracted attention due to the consumer's tendency to choose safety and healthy product. This phenomenon potentially stimulates the increase of organic product's demand and indicates the prospect of organic business is very promising in the future.…”
Section: Introductionmentioning
confidence: 99%